Reading Connects: The Interrelationships between School Libraries, CT, Multimodality and their Impacts on Reading Motivation and the Multiliteracy Development. - Lo, Patrick; Tsang, Ricky (International Journal of the Book, 2009)
According to Stephen Krashen (1993), "When children read for pleasure, when they get "hooked on books", they acquire involuntarily and without conscious effort, nearly all of the so-called "language skills" people are concerned about: They will become adequate readers, acquire a large vocabulary, develop the ability to understand and use complex grammatical constructions, develop a good writing style, and become good (but not necessarily perfect) spellers. Although free/voluntary reading alone will not ensure attainment of the highest levels of literacy, it will at least ensure an acceptable level. Without it, I suspect that children simply do not have a chance." Literacy has been a necessary prerequisite for functioning in society. People have read in order to fulfill occupational, community, and social needs. Some people also have read simply for pleasure of doing so. It has been determined that motivation significantly influences learning. Studies suggest that recreational or voluntary reading habits should be acquired fairly early in an individual's school life, probably in elementary school, given that numerous studies have shown a decline in time spent on reading that begins in middle school. Owing to this reason, educators, researchers, parents, as well as society have become increasingly interested in the role of reading engagement or reading motivation that actually plays in the growth of children's academic achievements, as well as their overall literacy developments. It is because children's literacy development determines children's future success in reading and writing, and researchers and teachers have explored the problem from various aspects, such as teaching methods, classroom environments, family involvement, and community and societal environment, etc. Different results have been found, and suggestions given in order to help develop children's literacy in and out of school. However, given the vast amount of research conducted on reading, it seems that little attention has been given to investigate children's actual reading motivation. A majority of research in reading focused on examining the cognitive aspects of reading instead. In addition, there is a common concern among reading educators that there is no agreement upon methods for language arts (reading, writing, and oral communication) instruction today. Although research has been conducted and concepts applied to teaching practices, there is no conclusive evidence that one method, such as basals, or whole langue, is the best. The purpose of this study is to present a review of selected literature that are devoted to discussing issues concerning elementary school students' reading practices and motivation in the age of digital communication, as well as examining the interrelationships between school libraries, ICT, multimodality and their impacts on reading motivation and the overall multi-literacy development amongst elementary-school students. This paper also includes case studies of two elementary international schools in Hong Kong, which share their experiences in the implementation of a series of reading incentive programmes at their school libraries via a newly acquired online audio-book resource (Naxos Spoken Word Library).